PEMETAAN KANTONG KEMISKINAN DAN POTENSI WILAYAH UNTUK PEMBERDAYAAN KELUARGA MISKIN PASCA COVID-19 DI KABUPATEN KONAWE SELATAN - Sinapoy, Muhammad Sabaruddin; Moita, Salsalman; Rihu, Agus; Keke, Ahmat; Almarsaban, Almarsaban; Kiro, Muhammad Ramadan (Fakultas Pertanian Universitas Halu Oleo, 2023)
Poverty mapping is carried out by examining the economic characteristics of a region and household, such as the poverty of families whose livelihoods are fishermen, farmers, miners, the informal sector, trade and services. This is relevant to the National Economic Recovery Program (PEN) as one of a series of activities to reduce the impact of Covid-19 on the economy, one of which is mapping pockets of poverty and recovery and empowerment policy strategies for the community, including poor families, both in rural and urban areas. The aim of this research is to examine the potential of the region and produce a Post-Covid-19 Poor Family Empowerment Strategy in South Konawe Regency. This research use desciptive qualitative approach. Referring to this design, this research was carried out in South Konawe Regency, using purportive sampling technique. The data collection techniques used were document study, in-depth interviews, questionnaires and observation. This research data processing and analysis uses two methods, namely quantitatively and qualitatively. The research results show that the socio-economic conditions of poor families in South Konawe Regency are reflected in several items, namely employment conditions, income level, house type, house size, ownership and use of toilets, clean water sources, lighting sources, education level, and types of side jobs. Of these items, there are only two different items that occurred in the research sample village communities both before the pandemic and after the pandemic. These items are employment conditions and income level. Regional Potential for Empowering Poor Families Post-Covid-19 is divided into traditional fishermen (fish catchers using simple technology) in Tinanggea District, plantation farmers and cultivators with very limited access to agricultural land in Benua District, informal sector workers in Andoolo District, stone miners traditional in North Moramo District and commuters (travel workers from out-of-town residents working in Kendari City) in Ranomeeto district. The Post-Covid-19 Poor Family Empowerment Strategy can be divided into several things, namely existing policies for poor families during the pandemic, developing KUBE, empowering the community through developing institutions and social capital, maximizing the use of village funds, and providing ease of obtaining KUR facilities.